Biocompatible Semiconductor Quantum Dots as Cancer Imaging Agents. Issue 18 (22nd February 2018) - McHugh, Kevin J.; Jing, Lihong; Behrens, Adam M.; Jayawardena, Surangi; Tang, Wen; Gao, Mingyuan; Langer, Robert; Jaklenec, Ana
Abstract: Approximately 1.7 million new cases of cancer will be diagnosed this year in the United States leading to 600 000 deaths. Patient survival rates are highly correlated with the stage of cancer diagnosis, with localized and regional remission rates that are much higher than for metastatic cancer. The current standard of care for many solid tumors includes imaging and biopsy with histological assessment. In many cases, after tomographical imaging modalities have identified abnormal morphology consistent with cancer, surgery is performed to remove the primary tumor and evaluate the surrounding lymph nodes. Accurate identification of tumor margins and staging are critical for selecting optimal treatments to minimize recurrence. Visible, fluorescent, and radiolabeled small molecules have been used as contrast agents to improve detection during real‐time intraoperative imaging. Unfortunately, current dyes lack the tissue specificity, stability, and signal penetration needed for optimal performance. Quantum dots (QDs) represent an exciting class of fluorescent probes for optical imaging with tunable optical properties, high stability, and the ability to target tumors or lymph nodes based on surface functionalization. Here, state‐of‐the‐art biocompatible QDs are compared with current Food and Drug Administration approved fluorophores used in cancer imaging and a perspective on the pathway to clinical translation is provided. Abstract : Near‐infrared quantum dots have the potential to serve as superior contrast agents for intraoperative optical imaging during tumor resection and lymph node biopsy compared with current dyes approved by the Food and Drug Administration. By modulating the size, composition, and surface functionalization, quantum dots can emit at wavelengths with superior tissue penetration and preferentially target a tumor or the lymph nodes to improve imaging contrast.